Protocols for Characterization of Cdk5 Kinase Activity. Issue 10 (22nd October 2021) - Terse, Anita; Amin, Niranjana; Hall, Bradford; Bhaskar, Manju; B.K., Binukumar; Utreras, Elias; Pareek, Tej K.; Pant, Harish; Kulkarni, Ashok B.
Abstract: Cyclin‐dependent kinases (Cdks) are generally known to be involved in controlling the cell cycle, but Cdk5 is a unique member of this protein family for being most active in post‐mitotic neurons. Cdk5 is developmentally important in regulating neuronal migration, neurite outgrowth, and axon guidance. Cdk5 is enriched in synaptic membranes and is known to modulate synaptic activity. Postnatally, Cdk5 can also affect neuronal processes such as dopaminergic signaling and pain sensitivity. Dysregulated Cdk5, in contrast, has been linked to neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS). Despite primarily being implicated in neuronal development and activity, Cdk5 has lately been linked to non‐neuronal functions including cancer cell growth, immune responses, and diabetes. Since Cdk5 activity is tightly regulated, a method for measuring its kinase activity is needed to fully understand the precise role of Cdk5 in developmental and disease processes. This article includes methods for detecting Cdk5 kinase activity in cultured cells or tissues, identifying new substrates, and screening for new kinase inhibitors. Furthermore, since Cdk5 shares homology and substrate specificity with Cdk1 and Cdk2, the Cdk5 kinase assay can be used, with modification, to measure the activity of other Cdks as well. © 2021 Wiley Periodicals LLC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Measuring Cdk5 activity from protein lysates Support Protocol 1 : Immunoprecipitation of Cdk5 using Dynabeads Alternate Protocol : Non‐radioactive protocols to measure Cdk5 kinase activity Support Protocol 2 : Western blot analysis for the detection of Cdk5, p35, and p39 Support Protocol 3 : Immunodetection analysis for Cdk5, p35, and p39 Support Protocol 4 : Genetically engineered mice (+ and – controls) Basic Protocol 2 : Identifying new Cdk5 substrates and kinase inhibitors